2022
DOI: 10.3390/v14040677
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Origins of Human Metapneumovirus: A Journey from Birds to Humans

Abstract: Metapneumoviruses, members of the family Pneumoviridae, have been identified in birds (avian metapneumoviruses; AMPV’s) and humans (human metapneumoviruses; HMPV’s). AMPV and HMPV are closely related viruses with a similar genomic organization and cause respiratory tract illnesses in birds and humans, respectively. AMPV can be classified into four subgroups, A–D, and is the etiological agent of turkey rhinotracheitis and swollen head syndrome in chickens. Epidemiological studies have indicated that AMPV also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 159 publications
0
13
0
Order By: Relevance
“…hMPV can be divided into four major genetic lineages (A1, A2, B1 and B2) [ 8 ]. The A2 lineage is the most genetically diverse and is further divided into A2a, A2b1 and A2b2.…”
Section: Introductionmentioning
confidence: 99%
“…hMPV can be divided into four major genetic lineages (A1, A2, B1 and B2) [ 8 ]. The A2 lineage is the most genetically diverse and is further divided into A2a, A2b1 and A2b2.…”
Section: Introductionmentioning
confidence: 99%
“…The American lineage of AMPV‐C was first detected in commercial turkey farms in the United States in 1996 (Kleven, 1997; Senne et al., 1997) with infections reported in multiple states including Colorado and later also in Minnesota, North Dakota, South Dakota, Iowa, and Wisconsin (Bennett et al., 2004; Goyal et al., 2000). Multiple reports of AMPV‐C infection of wild bird species has also been reported in the United States and Canada (Jesse et al., 2022), including a variety of duck species, snow geese ( Anser caerulescens ), Canada geese ( Branta Canadensis ), ring‐billed gulls ( Larus delawarensis ), house sparrow ( Passer domesticus ), barn swallow ( Hirundo rustica ), European starling (Sturnus vulgaris), and the blue‐winged teal ( Spatula discors ) (Bennett et al., 2002, 2004; Jardine et al., 2018; Shin et al., 2000). Two AMPV‐C strains isolated from pheasants in a live bird market in Korea were also found to display a high level of sequence identity to American lineage strains (Lee et al., 2007).…”
Section: Introductionmentioning
confidence: 98%
“…The American lineage of AMPV-C was first detected in commercial turkey farms in the United States in 1996 (Kleven, 1997;Senne et al, 1997) with infections reported in multiple states including Colorado and later also in Minnesota, North Dakota, South Dakota, Iowa, and Wisconsin (Bennett et al, 2004;Goyal et al, 2000). Multiple reports of AMPV-C infection of wild bird species has also been reported in the United States and Canada (Jesse et al, 2022), including a variety of duck species, snow geese (Anser caerulescens),…”
Section: Introductionmentioning
confidence: 99%
“…Different types of AMPVs have been classified based on the nucleotide sequence divergence of the attachment glycoprotein (G) and antigenic differences between strains (5). Types A and B are found all around the world, and type C was reported in North America, China, and South Korea, and in a retrospective study in France in 1990 (6).…”
Section: Introductionmentioning
confidence: 99%
“…Types A and B are found all around the world, and type C was reported in North America, China, and South Korea, and in a retrospective study in France in 1990 (6). Type D was reported only once in a turkey flock in France in 1985 (5,7). AMPV types A, B, and C have been detected in South Korea; the type A and B in poultry farms and the type C from pheasants in live bird markets (6,8,9).…”
Section: Introductionmentioning
confidence: 99%